Leonid Grigorian’s Letters - KUBATIAN, GEORGY (Bulletin of Yerevan University H: Russian Philology, 2021)
Leonid Grigorian (1929-2010) is a poet and translator of Armenian poetry and French prose. He was born in Rostov-on-Don and lived in this city all his life. His poems were regularly published in popular magazines "Novy mir", "Znamya", "Zvezda" etc., reviews on his books were written by leading Russian critics. L. Grigorian translated (from the interlinear translation) the poems of Armenian poets, including R. Davoyan, G. Emin and H. Shiraz, as well as our French-writing compatriots Armen Lubin and Vahé Godel. The stories, novels and dramas of A. Camus and J. P. Sartre, as well as Vahé Katcha’s novel "Dagger in the Garden", dedicated to the Armenian genocide, were published in magazines and books. Тhe letters to his Yerevan friend Georgi Koubatian describe some of the circumstances of his literary biography, contain a number of original thoughts and appraisals.